Intraoperative methylene blue testing for female urethral diverticulum: diagnostic value and surgical outcomes - Aldakhil, Lateefa (Frontiers in Urology, 2026)
BackgroundFemale urethral diverticulum (UD) is a rare and often underdiagnosed condition that mimics other lower urinary tract disorders, leading to diagnostic delays. This study evaluated the clinical presentation, diagnostic accuracy, and surgical outcomes of methylene blue-assisted cystourethroscopy as an adjunct tool in confirming and localizing UD.MethodsFifteen female patients suspected of UD between 2015 and 2025 were retrospectively reviewed. All underwent cystourethroscopy with intraoperative methylene blue dye injection. Diagnostic findings were correlated with final histopathology, and surgical outcomes were assessed following transvaginal diverticulectomy.ResultsTwelve patients (80%) had histologically confirmed UD, while three had non-diverticular lesions (two Skene’s gland cysts and one vaginal mucosa cyst). The methylene blue test was positive in 11 of 12 UD cases, yielding 91.7% sensitivity, 100% specificity, and 93.3% overall diagnostic accuracy. Most diverticula were mid-urethral (66.6%). Postoperatively, 83.3% achieved complete symptom resolution, while recurrence (16.7%) and fistula (8.3%) were successfully managed. No new stress incontinence or urethral stricture occurred.ConclusionMethylene blue-assisted cystourethroscopy is a simple, accurate, and low-cost adjunct that enhances intraoperative diagnosis and localization of female UD. It may be helpful in resource-limited settings. However, its role remains adjunctive, as it cannot replace MRI in defining complex anatomy. The small sample size, retrospective design, and inconsistent imaging represent key limitations. Larger prospective studies are needed to validate these findings.